2021
DOI: 10.1007/s11164-021-04560-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic, electrical and optical properties of potassium borate (KB5O8·4H2O) hydrothermally synthesized from different boron sources

Abstract: Potassium borate was hydrothermally synthesized from various boron minerals (H 3 BO 3 , B 2 O 3 , Na 2 B 4 O 7 •5H 2 O and Na 2 B 4 O 7 •10H2 O) at reaction conditions of 60-90 °C and 15-120 min. The synthesized potassium borate was identified as "santite (KB 5 O 8 •4H 2 O)" from the X-ray diffraction (XRD) analyses results. The specific band values between B and O atoms were characterized by Fourier transform infrared and Raman spectroscopies. Multiangular particles were generally observed in the range of 3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Bands corresponding to the symmetric stretching of four coordinate boron to oxygen bands [ ν s (B (4) –O)] and the bending mode of boron–oxygen–hydrogen [ δ (B–O–H)] appear at 781 cm −1 and 1245 cm −1 in the FTIR spectrum of ZnB doped PEDOT:PSS thin films. 38 From the FTIR spectra, it is confirmed that dopants are substituted into the PEDOT:PSS lattice. 36…”
Section: Resultsmentioning
confidence: 94%
“…Bands corresponding to the symmetric stretching of four coordinate boron to oxygen bands [ ν s (B (4) –O)] and the bending mode of boron–oxygen–hydrogen [ δ (B–O–H)] appear at 781 cm −1 and 1245 cm −1 in the FTIR spectrum of ZnB doped PEDOT:PSS thin films. 38 From the FTIR spectra, it is confirmed that dopants are substituted into the PEDOT:PSS lattice. 36…”
Section: Resultsmentioning
confidence: 94%